IMPLEMENTASI PRINSIP EKONOMI KERAKYATAN DALAM PENGELOLAAN BANDARA INTERNASIONAL LOMBOK - John Abraham Ziswan Suryosumunar; Made Astriana Aristisari (Institut Agama Hindu Negeri Gde Pudja Mataram, 2022)
This research is a study in philosophy of economics that tried to analyze the implementation of Indonesian democratic economy (ekonomi kerakyatan) principle on Lombok International Airport management with philosophical hermeneutic method. Data used originated from observation data and interviews and also library research that related with the object of this research. The discussion is produced conclusions as below: (1) Indonesian democratic economy is a pillar of Indonesia's economy that based on social justice principle and partiality to society. (2) One of the problems of airport management in Indonesia is a stereotype about users of air transportation departure identified as middle to high social class and don’t provided facilities for people around. (3) Angkasa Pura I (Persero) as Lombok International Airport manager implements Indonesian democratic principle for positioning this airport as a place to develops the public economy with provided facilities to street vendors and MSMEs. This efforts is to create social justice for public especially the people of West Nusa Tenggara